The Ferns of the Calilegua National Park: a look through their spores. Part I - Gorrer, Daniel Alejandro (2023)
Calilegua National Park is located in the Southeast of the province of Jujuy, Argentina. It is comprised of different districts within the Yungas Biogeographic Province, where conditions are optimal for fern development. The palynological studies with light microscopy in this area are very limited. The aim of this work is to present the morphology of spores from 42 taxa belonging to 9 families of isosporate ferns that grow in this protected area. The study was carried out with herbarium material. The families studied are Anemiaceae, Aspleniaceae, Athyriaceae, Blechnaceae, Cyatheaceae, Cystopteridaceae, Dennstaedtiaceae, Dryopteridaceae, and Equisetaceae. According to the spore aperture type, 35 taxa are monolete, five trilete, and two alete. The spores are yellowish, light to dark brown or brown greenish. The largest spores belong to Anemia australis and the smallest to Asplenium argentinum. Equinate, folded, cristate, alate, reticulate, ridged, psilate, verrucate, and baculate spores were observed. For the first time, the spores of 27 species are illustrated under a light microscope. An identification key of the spores is also provided. The morphological characteristics of the spores allowed for the identification of 23 species, contributing to spore bank analysis, aeropalynological and paleopalynological studies, and taxonomic identifications.